Edukasi Stunting sebagai Upaya Meningkatkan Pemahaman Ibu tentang Dampak Stunting terhadap Pendidikan Anak di Desa Kubang Utara Sikabu - Sandra Dewi; Anggie Kurnia Putri; Fakhri Taufiqul Hakim; Ostari Fayane; Widia Khairun Afni (CV. ITTC INDONESIA, 2025)
Stunting is a growth disorder in toddlers characterized by a height lower than that of an average child for their age. It results from prolonged nutritional deficiencies, especially during critical periods of their lives. Stunting also carries the risk of diminishing a child's intellectual abilities. This research employed a quantitative approach using a one-group pretest-posttest design. The low level of awareness and understanding among mothers in rural areas regarding stunting and its impact on children's academic achievement indicates the necessity for educational interventions that can bridge the community's understanding of the importance of nutrition and child care to support their educational success. Based on the pre-test, out of 15 respondents, 6 individuals (40%) had a poor level of knowledge, 6 (40%) were in the moderate category, and 3 (20%) had good knowledge regarding stunting prevention. After the education was conducted, the post-test results showed a significant improvement. The number of respondents in the poor knowledge category decreased to 0%. The moderate category remained at 6 individuals (40%). In the good category, the number increased from 3 individuals (20%) to 9 individuals (60%). This change indicates that the education provided successfully increased the knowledge of mothers of toddlers regarding stunting. With this enhanced understanding, mothers are expected to take more appropriate preventive measures, such as providing adequate nutritional intake and paying attention to their child's growth and development from an early age. This is crucial, given that the mother's role as the primary caregiver significantly influences the quality of a child's future health and education.